2013
DOI: 10.4236/wjcd.2013.37072
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell count and mortality in acute myocardial infarction

Abstract: Introduction: Coronary atherosclerosis is increasingly viewed as an inflammatory process. We assessed the relation between WBC count on admission and mortality in STEMI patients treated with primary PCI. Material & Method: Totally 205 patients with STEMI less than 24 hours before admission who admitted for primary angioplasty enrolled in study. Study end points were defined as myocardial adverse cardiac event (MACE) and mortality at one month and one year follow-up. Result: Totally 205 patients (166 men) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several studies have reported the association of total leukocyte count with the incidence and adverse outcome of CAD. [3][4][5] Adiponectin is a protein hormone secreted by white adipose tissue and is one of the agents which may be involved in the protection of coronary vessels from atherosclerosis. Serum adiponectin concentrations range from 3-30 μg/mL, and is observed to be reduced with obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported the association of total leukocyte count with the incidence and adverse outcome of CAD. [3][4][5] Adiponectin is a protein hormone secreted by white adipose tissue and is one of the agents which may be involved in the protection of coronary vessels from atherosclerosis. Serum adiponectin concentrations range from 3-30 μg/mL, and is observed to be reduced with obesity.…”
Section: Introductionmentioning
confidence: 99%